(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The present study is conducted to understand the significance of vocabulary learning. Vocabulary learning is the root of English language learning which reinforces other skills of English language learning. The study is qualitative in nature, based on the review of the previous studies, and conducted to understand the significance of vocabulary learning of English language in Pakistani context. The findings show that vocabulary learning is extremely necessary for English language learning process in Pakistan but it requires proper planning, revision of traditional methods and the need of teachers’ equipment with such techniques that could enable a student’s effective learning. Provision of exercises and content can also be helpful in enhancing the vocabulary learning process of English language in Pakistan.